Effects of a Probiotic Formulation on Seasonal Allergic Rhinitis in Adults—A Randomized Double-Blind Placebo-Controlled Trial: The Probiotics for Hay Fever Trial - Ried, Karin; Travica, Nikolaj; Paye, Yeah; Sali, Avni (Frontiers in Nutrition, 2022)
Background Seasonal-allergic-rhinitis (hay fever) affects approximately 4.6 million (20%) Australians each year. Hay fever manifests as runny/blocked nose and often itchy/sore/swollen eyes, with symptoms greatly impacting the quality of life. Rescue medications such as antihistamines are often needed to restore function, but they may trigger some other unwanted side effects. Probiotics have shown promise to reduce hay fever symptoms. Objective In this randomized double-blind placebo-controlled 12-week trial, we aimed to assess the tolerability and efficacy of the probiotic formula “NC-Seasonal-Biotic” on symptoms, quality-of-life, and immunological and microbial factors. Methods Adults, who had previously suffered from hay fever symptoms, were screened for eligibility and randomly allocated to probiotic or placebo trial powder. Treatment effectiveness was assessed by questionnaires, daily total-nasal-symptom-score, and weekly rhinoconjunctivitis quality-of-life questionnaire. Secondary outcome measures included immunological parameters such as T-cell immunity (Th1/Th2 ratio) and the stool-microbiome analysis. Tolerability was assessed weekly by the gastrointestinal symptom scale. Results Recruitment and follow-up were challenging around the 2020/2021 hay fever season in Melbourne, Australia, due to the harsh COVID-19 restrictions and extended lockdowns. Out of the 82 adults enrolled in this study, 75% participated (n = 60), and half (n = 40) completed the 10–12-week intervention period. In the intention-to-treat analysis, no significant differences in hay fever symptoms were apparent between the groups, while quality-of-life trended toward greater improvement in the active group. Intention-to-treat analysis was confounded due to a third of all participants not completing the full 10–12-week-intervention period. Subgroup analyses of the participants (n = 40) completing the full 10–12-week study period revealed a significantly greater reduction in symptoms in the active group compared with the placebo group, including runny nose (p = 0.04) and itchy eyes (p = 0.01). Furthermore, the active group reported significant improvements in the quality-of-life, including more functionality during the day (p = 0.05), better sleep (p = 0.005), less fatigue (p = 0.04), less thirst (p = 0.007), and less irritability (p = 0.007). Immunological parameters, measured by T-helper cell ratio (Th1/Th2), improved significantly in the active group compared with the placebo group. Most microbial changes were not statistically different between the groups. The trial powder was generally well tolerated. Conclusion Our study suggests the probiotic formula “NC-Seasonal-Biotic,” taken for 10–12 weeks, as effective in reducing hay fever symptoms, such as runny nose and itchy eyes, and improved the quality-of-life and immunological parameters while being well tolerated. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [ACTRN126200 01078943].